2014
DOI: 10.1002/ajim.22375
|View full text |Cite
|
Sign up to set email alerts
|

Gender in occupational health research of farmworkers: A systematic review

Abstract: BackgroundFarmwork is one of the most hazardous occupations for men and women. Research suggests sex/gender shapes hazardous workplace exposures and outcomes for farmworkers. This paper reviews the occupational health literature on farmworkers, assessing how gender is treated and interpreted in exposure-outcome studies.MethodsThe paper evaluates peer-reviewed articles on men and women farmworkers' health published between 2000 and 2012 in PubMed or SCOPUS. Articles were identified and analyzed for approaches t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 68 publications
1
27
0
1
Order By: Relevance
“…A study 8 found that living in rural areas, common among farm workers, was associated with maternal death. Farming jobs are characterized by high physical demands in almost all tasks performed, in addition to exposure to excessive heat 27 , contact with pesticides 28 -many of which are endocrine disruptors 29 -materials and biological agents 30,31 and animal injuries 31 , among other factors that affect health. Little is known about the working conditions of farm worker women in Brazil, but an important feature is the "naturalization" of occupation, commonly considered only as "help" and not a true job.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study 8 found that living in rural areas, common among farm workers, was associated with maternal death. Farming jobs are characterized by high physical demands in almost all tasks performed, in addition to exposure to excessive heat 27 , contact with pesticides 28 -many of which are endocrine disruptors 29 -materials and biological agents 30,31 and animal injuries 31 , among other factors that affect health. Little is known about the working conditions of farm worker women in Brazil, but an important feature is the "naturalization" of occupation, commonly considered only as "help" and not a true job.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the working conditions of farm worker women in Brazil, but an important feature is the "naturalization" of occupation, commonly considered only as "help" and not a true job. Therefore, women who work in agriculture, are not likely to be recognized as farm worker, being informed about occupational risks they face and how to prevention them, or whether exposed how they will compromise their health 30,31 . Access to adequate medical care, such as prenatal care, is commonly lower in rural areas 32 , where precarious quality and provision of health services also prevail, which deserves further specific studies.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, sex and gender play an important role in occupational health. In the workplace, women and men can have different work exposures and health outcomes because of differences in job assignments and work tasks [ 19 , 20 , 21 ]. The gendered segregation of jobs and tasks are often influenced by societal roles, stereotypes, and expectations [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…While one in five farmworkers are women or partnered with farmworkers (59% of farmworkers are married or cohabitating) (Carroll et al, 2011), much of the literature does not explore how relationships between exposure and outcomes are shaped by gender (Habib et al, 2014). Our findings suggest that women, who are often primary caregivers in addition to their part-time or full-time work, may face additional challenges.…”
Section: Discussionmentioning
confidence: 99%